Comparison of two label-free global quantitation methods, APEX and 2D gel electrophoresis, applied to the Shigella dysenteriae proteome. - Kuntumalla, Srilatha.; Braisted, John C.; Huang, Shih-Ting.; Parmar, Prashanth P.; Clark, David J.; Alami, Hamid.; Zhang, Quanshun.; Donohue-Rolfe, Arthur.; Tzipori, Saul.; Fleischmann, Robert D.; Peterson, Scott N.; Pieper, Rembert. (2016)
Abstract: The in vitro stationary phase proteome of the human pathogen Shigella dysenteriae serotype 1 (SD1) was quantitatively analyzed in Coomassie Blue G250 (CBB)-stained 2D gels. More than four hundred and fifty proteins, of which 271 were associated with distinct gel spots, were identified. In parallel, we employed 2D-LC-MS/MS followed by the label-free computationally modified spectral counting method APEX for absolute protein expression measurements. Of the 4502 genome-predicted SD1 proteins, 1148 proteins were identified with a false positive discovery rate of 5% and quantitated using 2D-LC-MS/MS and APEX. The dynamic range of the APEX method was approximately one order of magnitude higher than that of CBB-stained spot intensity quantitation. A squared Pearson correlation analysis revealed a reasonably good correlation (R 2 = 0.67) for protein quantities surveyed by both methods. The correlation was decreased for protein subsets with specific physicochemical properties, such as low Mr values and high hydropathy scores. Stoichiometric ratios of subunits of protein complexes characterized in E. coli were compared with APEX quantitative ratios of orthologous SD1 protein complexes. A high correlation was observed for subunits of soluble cellular protein complexes in several cases, demonstrating versatile applications of the APEX method in quantitative proteomics.; Keywords: two-dimensional electrophoresis, Absolute protein expression, Attribute relation file format, Coomassie Brilliant Blue, False positive rate, Isoelectric focusing, Laboratory Information Management System, Liquid chromatography with tandem mass spectrometry, Matrix-assisted laser desorption ionization with tandem time of flight, Mass spectrometry, Methyl methanethiosulfonate, protein molecular weight, estimation of expected number of unique proteotypic peptides for a given protein i, protein isoelectric point, squared Pearson correlation coefficient, Spearman rank correlation coefficient, Room temperature, Shigella dysenteriae type 1, Triethyl ammonium bicarbonate, (Tris(2-carboxyethyl)phosphine).; Springer Open.